In vivo effects of PCB-126 and genistein on vitellogenin expression in zebrafish. Issue 17 (2nd September 2019) - Licata, Patrizia; Tardugno, Roberta; Pergolizzi, Simona; Capillo, Gioele; Aragona, Marialuisa; Colombo, Antonio; Gervasi, Teresa; Pellizzeri, Vito; Cicero, Nicola; Calò, Margherita
Abstract: In this study, the vitellogenin (Vtg) modulation by genistein and polychlorinated biphenyl-126 (PCB-126) exposure in zebrafishes has been investigated. Both PCB-126 and genistein have been identified as aquatic pollutants and can further increase estrogenicity of waterways. Vtg is egg yolk precursor protein release by the hepatocytes during vitellogenesis. This process occurs normally in the hepatocytes in response to the activation with the estrogens such as 17-β-estradiol. Our immunohistochemical findings showed a Vtg expression that increases at 12 h and at 72 h in the liver of treated fishes with both PCB-126 and genistein, individually and in combination. Furthermore, for the first time, also hepatic stellate cells (HSC) in the liver parenchyma were strongly positive for vitellogenin. Abstract :